2022
DOI: 10.1186/s13578-021-00738-7
|View full text |Cite
|
Sign up to set email alerts
|

Turning the tide on Alzheimer’s disease: modulation of γ-secretase

Abstract: Alzheimer’s disease (AD) is the most common type of neurodegenerative disorder. Amyloid-beta (Aβ) plaques are integral to the “amyloid hypothesis,” which states that the accumulation of Aβ peptides triggers a cascade of pathological events leading to neurodegeneration and ultimately AD. While the FDA approved aducanumab, the first Aβ-targeted therapy, multiple safe and effective treatments will be needed to target the complex pathologies of AD. γ-Secretase is an intramembrane aspartyl protease that is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…Table 1 outlines the current status of clinical trials among these agents by targeting secretase and amylin [ 67 , 110 , 120 , 121 , 122 , 123 , 126 , 150 ]. Moreover, the findings of this review with regard to α-secretase activators, β-secretase inhibitors, γ-secretase inhibitors, and amylin agonists align with the findings of previous reviews but also build upon with recent evidence on small peptide therapeutics as well [ 27 , 72 , 149 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. This is encouraging given the current development of newer of AD therapeutics outside of small peptides.…”
Section: Discussionsupporting
confidence: 80%
“…Table 1 outlines the current status of clinical trials among these agents by targeting secretase and amylin [ 67 , 110 , 120 , 121 , 122 , 123 , 126 , 150 ]. Moreover, the findings of this review with regard to α-secretase activators, β-secretase inhibitors, γ-secretase inhibitors, and amylin agonists align with the findings of previous reviews but also build upon with recent evidence on small peptide therapeutics as well [ 27 , 72 , 149 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. This is encouraging given the current development of newer of AD therapeutics outside of small peptides.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, Aβ38 has an inhibitory effect on fibril formation, but the most significant effect was observed by the proportion of 1:3:2 or 1:4:1 of Aβ 1-40/Aβ38/Aβ37 [38]. This and other studies appear to indicate a therapeutic target related to γ-secretase modulators, which could reduce Aβ plaque formation [35,39,40]. There have been several promising attempts to use other conformations.…”
Section: Molecular Neuropathology Of Alzheimer's Disease and Related ...mentioning
confidence: 73%
“…Recent evidence has suggested that aberrant Notch signaling could result in the neurodegeneration seen in AD ( Woo et al, 2009 ; Kapoor and Nation, 2021 ). In addition, the failure of γ-secretase inhibitors as treatments of AD has been partly attributed to its deleterious effects on Notch signaling, which may have counteracted any benefits from reduced Aβ production ( Luo and Li, 2022 ). MGAT5 was implicated as part of Golgi metabolic pathways and has attracted recent interest due to its human-specific differential expression in brain tissue layers as well as in AD ( Jorge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%